2018
DOI: 10.1038/s41598-018-36388-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Metabolic Syndrome Model Associated with Mechanical and Structural Degenerative Changes of the Aortic Valve

Abstract: The purpose of this study was to test the hypothesis that an experimental high fat (HF) animal with metabolic syndrome results in structural degeneration of the aortic valve. Domestic pigs were divided (n = 12) and administered either a normal or HF diet. After 16-weeks, the HF diet group had increased weight (p ≤ 0.05), total cholesterol (p ≤ 0.05), and systolic and diastolic pressure (p ≤ 0.05). The aortic valve extracellular matrix showed loss of elastin fibers and increased collagen deposition in the HF di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…In patients with the bicuspid aortic valve, which is the most common congenital heart disease occurring in 1%-2% of the population, AS development occurs statistically more frequently [2]. Growing evidence indicates that diabetes mellitus (DM) can increase the risk of AS development and the rate of AS progression [4][5][6][7][8][9][10][11]. The diagnosis of AS is based on echocardiographic assessment.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with the bicuspid aortic valve, which is the most common congenital heart disease occurring in 1%-2% of the population, AS development occurs statistically more frequently [2]. Growing evidence indicates that diabetes mellitus (DM) can increase the risk of AS development and the rate of AS progression [4][5][6][7][8][9][10][11]. The diagnosis of AS is based on echocardiographic assessment.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, canine models do not show all the components of MetS because the development of endothelial damage or fasting hyperglycaemia in dogs is questionable. In addition, porcine models present high anatomical and physiological similarity with humans [18,21,22]. Therefore, they can offer significant predictive power for MetS components, but their maintenance and need for trained personnel and complex resources for experimental procedures make porcine models very laborious and expensive to use [16].…”
Section: Introductionmentioning
confidence: 99%
“…These alterations occur simultaneously, increasing the risk of adverse events and leading to the association of metabolic syndrome with the progression of DAS irrespective of traditional risk factors [73]. Furthermore, experimental models have demonstrated that metabolic syndrome is as-sociated with mechanical and structural changes of the AV and early calcification [74]. Alternatively, there are reports that patients with metabolic syndrome manifest a greater risk of developing DM [75].…”
Section: Metabolic Syndromementioning
confidence: 99%